An Observational Case Study of One Third Grade Teacher's Taught Social and Emotional Skills Curriculum - (:unkn) unknown (My University, 2013)
The development of social and emotional (SE) skills: self-awareness, self-management, decision making, relationship skills, and social awareness, can enhance school engagement and reduce relational aggression (CASEL, 2007). Yet, many schools do not provide a written or supported SE skills curriculum. This observational case study explored one teacher's taught SE skills curriculum. The research questions which guided the study are:

*What taught social and emotional skills curriculum does a third-grade elementary school teacher deliver in a self-contained classroom?

*In what way does a third-grade elementary school teacher deliver the taught social and emotional skills curriculum in a self-contained classroom?

*What impact does the taught social and emotional curriculum have on the development of the class's social and emotional skills of self-awareness, self-management, social awareness, relationship building, and responsible decision making?

The study's findings suggested that a teacher can teach social and emotional skills without a written or supported curriculum. However, the SE skills teaching instruction needs to align with a theory of learning. Specifically, the students are provided with an opportunity to (a) engage in teacher-with-student and student-with-student dialogue and (b) experience peer social interaction in their peer culture.

One recommendation for further research would be to conduct a case study in which the researcher observes student-student teaching of the SE skills.
Keywords: Social skills in children--Study and teaching--Case studies; Emotional intelligence--Study and teaching (Primary)--Case studies; Social intelligence--Study and teaching (Primary)--Case studies